2012
DOI: 10.1021/es204142e
|View full text |Cite
|
Sign up to set email alerts
|

NOx and N2O Precursors from Biomass Pyrolysis: Nitrogen Transformation from Amino Acid

Abstract: Large quantities of NO(x) and N(2)O emissions can be produced from biomass burning. Understanding nitrogen behavior during biomass pyrolysis is crucial. Nitrogen in biomass is mainly in forms of proteins (amino acids). Phenylalanine, aspartic acid, and glutamic acid were used as the model compounds for the nitrogen in biomass. Release behavior tests of nitrogen species from the three amino acids during pyrolysis in argon and gasification with O(2) and CO(2) were performed using a thermogravimetric analyzer (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 20 publications
2
65
0
Order By: Relevance
“…Given the predominance of proteins as the main nitrogen-containing compound in biomass, some researchers [172][173][174][175][176][177] have used amino acids as model compounds to study the behavior of nitrogen during thermal decomposition of biomass. Ren and Zhao [175] studied the pyrolysis and O 2 and CO 2 gasification behavior of phenylalanine, aspartic acid and glutamic acid in a TGA at temperatures ranging from 0 K to1073 K. The distinct structures of these amino acids cause them to behave slightly differently under argon pyrolysis as well as O 2 and CO 2 gasification.…”
Section: Fuel Nitrogen Behavior During Biomass Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the predominance of proteins as the main nitrogen-containing compound in biomass, some researchers [172][173][174][175][176][177] have used amino acids as model compounds to study the behavior of nitrogen during thermal decomposition of biomass. Ren and Zhao [175] studied the pyrolysis and O 2 and CO 2 gasification behavior of phenylalanine, aspartic acid and glutamic acid in a TGA at temperatures ranging from 0 K to1073 K. The distinct structures of these amino acids cause them to behave slightly differently under argon pyrolysis as well as O 2 and CO 2 gasification.…”
Section: Fuel Nitrogen Behavior During Biomass Conversionmentioning
confidence: 99%
“…Ren and Zhao [175] studied the pyrolysis and O 2 and CO 2 gasification behavior of phenylalanine, aspartic acid and glutamic acid in a TGA at temperatures ranging from 0 K to1073 K. The distinct structures of these amino acids cause them to behave slightly differently under argon pyrolysis as well as O 2 and CO 2 gasification. Ren et al [176] found that the structure of the amino acids, the mineral matter content of biomass [178,179], the pyrolysis/gasification condition and the particle size [161,180] affects significantly the fate of nitrogen during pyrolysis of biomass.…”
Section: Fuel Nitrogen Behavior During Biomass Conversionmentioning
confidence: 99%
“…The thermal stability is dependent on the amino acid structure, and due to the different structures of amino acids. The behavior of nitrogen conversion is distinctive for different amino acids [191][192][193][194][195][196]. For some amino acids, HCN is the main N-containing species and its yield is higher, and for some amino acids, NH 3 is the main N-containing species.…”
Section: General Characteristics Of Protein/amino Acid Pyrolysismentioning
confidence: 99%
“…Undoubtedly, the release of NO can be attributed to the reaction between N-containing compounds and Å OH radicals (Ren and Zhao, 2012). A bimodal shape was observed for the NO emissions.…”
Section: Key N-containing Species Release Characteristicsmentioning
confidence: 94%
“…The second region (>400°C) was due to the secondary oxidation of N-containing residues derived from the primary degradation process. Compared with the N 2 atmosphere, the release of N species during the high temperature region was enhanced by the hydroxyl radical ( Å OH) derived from the cleavage of C-OH bonds in the presence of an air atmosphere (Ren and Zhao, 2012).…”
Section: Key N-containing Species Release Characteristicsmentioning
confidence: 99%